Pestalotiopsis phyllostachydis sp. nov. from Guangdong, China - Zhao, Haijun; Shu, Yongxin; Doilom, Mingkwan; Zeng, Xiangyu; Zhang, Huang; Dong, Wei (Phytotaxa, 2024)
Pestalotiopsis phyllostachydis sp. nov. is introduced during a study of the diversity of bambusicolous fungi in Guangdong Province, China. The new species exhibits similar conidial morphology, pigmentation, and dimensions to its relatives; however, it can be distinguished by the length of its apical and basal appendages. The identification is corroborated by a phylogenetic analysis incorporating combined ITS, tef1-α and tub2 sequence data. A refined description and illustration of P. phyllostachydis are provided, accompanied by a morphological comparison of this new taxon and its closely related taxa compiled in a table. In addition, the common morphological characteristics utilized for interspecific identification are discussed incidentally.